2017
DOI: 10.1016/j.cub.2017.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Melanopsin Contributions to the Representation of Images in the Early Visual System

Abstract: SummaryMelanopsin photoreception enhances retinal responses to variations in ambient light (irradiance) and drives non-image-forming visual reflexes such as circadian entrainment [1, 2, 3, 4, 5, 6]. Melanopsin signals also reach brain regions responsible for form vision [7, 8, 9], but melanopsin’s contribution, if any, to encoding visual images remains unclear. We addressed this deficit using principles of receptor silent substitution to present images in which visibility for melanopsin versus rods+cones was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 50 publications
5
93
0
1
Order By: Relevance
“…However, this study and a recent one [17] employing a similar system find that non-visual responses can be manipulated with a modified VDU with more than three primaries. Additionally, there is more and more evidence that melanopsin contributes to “classical” visual functions such as the perception of brightness [22, 37], colour [9, 38], space (humans: [9]; mice: [39]), and other visual attributes (humans: [24], mice: [4042]). It remains an interesting question to what extent the classical colour matching functions, which are the basis of our current cone fundamentals, reflect the activity of melanopsin (though the amount of rod contributions have been discussed extensively [43]).…”
Section: Discussionmentioning
confidence: 99%
“…However, this study and a recent one [17] employing a similar system find that non-visual responses can be manipulated with a modified VDU with more than three primaries. Additionally, there is more and more evidence that melanopsin contributes to “classical” visual functions such as the perception of brightness [22, 37], colour [9, 38], space (humans: [9]; mice: [39]), and other visual attributes (humans: [24], mice: [4042]). It remains an interesting question to what extent the classical colour matching functions, which are the basis of our current cone fundamentals, reflect the activity of melanopsin (though the amount of rod contributions have been discussed extensively [43]).…”
Section: Discussionmentioning
confidence: 99%
“…The appearance was curiously unpleasant. 292 The diffuse, even blurry, property of the percept might be related to the broad receptive 293 fields of neurons driven by melanopsin stimulation, 28 consistent with the extensive dendritic 294 arbors of the ipRGCs. 29 In a prior study, subjects reported that lights appear brighter when 295 melanopsin contrast is added to the stimulation of the cone-based luminance channel.…”
mentioning
confidence: 81%
“…25 Visual stimuli 26 We used the method of silent substitution with a digital light synthesis engine (OneLight Spec-27 tra) to stimulate targeted photoreceptors. Our device produces stimulus spectra as mixtures 28 Human cortical responses to melanopsin 1/14 of 56 independent,~16 nm full-width half-max primaries under digital control, and can modu- 29 late between these spectra at 256 Hz. Details regarding the device, stimulus generation, and 30 estimates of precision have been previously reported.…”
mentioning
confidence: 99%
“…This photic response is then transferred to nonvisual brain areas, including hypothalamic nuclei notably involved in circadian rhythmicity, and sleep-wake regulation 14,15 . IpRGC signals also reaches parts of brain primarily mediating vision, such as the lateral geniculate nucleus of the thalamus 13,15 and studies suggest that ipRGCs contribute to crude vision, brightness detection, and adjustment of rod and cones sensitivities [16][17][18][19][20][21] . Similarly to animal models, many human non-visual responses to light are more sensitive to shorter wavelength (blue) light exposures making them likely to be under ipRGC influence 5,[22][23][24][25][26] .…”
Section: The Discovery Of Intrinsically Photosensitive Retinal Ganglimentioning
confidence: 99%
“…Similarly to animal models, many human non-visual responses to light are more sensitive to shorter wavelength (blue) light exposures making them likely to be under ipRGC influence 5,[22][23][24][25][26] . Isolating ipRGCs and melanopsin roles from those of rods, cones and other RGCs can be achieved in animals by knocking down, amplifying, or modifying part of the photoreception system 19,27,28 . The exact role of ipRGCs remains difficult to isolate in humans, however, where specific genotypes perturbing the different parts of the retinal photoreception system are not available.…”
Section: The Discovery Of Intrinsically Photosensitive Retinal Ganglimentioning
confidence: 99%